A new approach to contour error control in high speed machining. (January 2015) - Rahaman, Mostafizur; Seethaler, Rudolf; Yellowley, Ian
Abstract: High speed machining technology attempts to maximize productivity through the use of high spindle speeds and axis traverse rates. The technology is dependent upon the development of suitable mechanical hardware, electrical drives and associated control software to ensure that all components are used to maximum advantage. The role of the control software is particularly demanding since one needs to maximize traverse rates while providing the necessary accuracy, and indeed providing a margin of safety to deal with unexpected changes in process, or system parameters. There have been relatively few improvements in commercial CAD or CAM systems that would help machine tool users to take maximum advantage of high speed machining; rather the majority of the approaches have been undertaken at the machine tool controller level. This paper uses circular interpolation and corner tracking to compare several such control techniques, (Cross Coupled Control (CCC), Zero Phase Error Tracking Control (ZPETC), and Realtime Frequency Modulated Interpolation (FMI)), each of which have been proposed in the literature order to improve machining accuracy. None of these approaches are found to be universally successful when used alone and the authors, in this paper, examine the use of these systems in combination. Particular attention is focused upon an extension of a simplified version of cross coupled control together with Frequency Modulated Interpolation. It is shown that the combined system performs extremely well, and is easily actuated at high frequencies with conventional hardware. A custom built high speed x-y table is used to confirm system performance with multiple constraints present.